ANALISIS PERTIMBANGAN HAKIM DALAM MENERAPKAN PASAL 28 AYAT (2) JO. PASAL 45A AYAT (2) UU ITE TERHADAP TINDAK PIDANA YANG DITUJUKAN KEPADA GOLONGAN ATAU ANTARGOLONGAN - Himawan, Geraldo; Rospita Adelina Siregar; Radisman Saragih (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Hate speech against the Indonesian Doctors Association (IDI) as an organization has been decided through Decision Number 828/Pid.Sus/2020/Pn.Dps, in which the panel of judges included IDI in the intergroup category as regulated in Article 28 paragraph (2) of the Law. ITE. However, the meaning between groups has a very broad meaning, causing legal uncertainty. The research method used is a normative juridical research method with a statute approach and a case study approach. The author analyzes and describes how the inter-group concept arrangements contained in Article 28 paragraph (2) of the ITE Law and how the judges consider in applying Article 28 paragraph (2) of the ITE Law in Decision Number 828/Pid.Sus/2020/Pn.Dps The results obtained by the author from this study include: (1) the groups contained in Article 28 paragraph (2) of the ITE Law and Article 45A paragraph (2) of the ITE Law contain the meaning of protecting entities that are not included in the scope of ethnicity, religion, and race (2) The judge’s legal considerations in applying Article 28 Paragraph (2) in conjunction with Article 45a Paragraph (2) of the ITE Law are in accordance with the elements contained in the article and are in accordance with the Constitutional Court Decision Number 76/PUU-XV/ 2017